Cytotoxicity and hormonal activity of glyphosate-based herbicides. (October 2020) - Tóth, Gergő; Háhn, Judit; Radó, Júlia; Szalai, Diána A.; Kriszt, Balázs; Szoboszlay, Sándor
Abstract: Glyphosate-based herbicides (GBHs) are the most widely used pesticides for weed control. In parallel with the renewal of the active ingredient, polyethoxylated POE(15) containing GBHs were banned in the EU in 2016. Since then, co-formulants were changed and numerous GBHs are marketed with different excipients declared as inert substances. In our study, we focused to determine acute and chronic cytotoxicity (by Aliivibrio fischeri assay) and direct hormonal activity (estrogenic and androgenic effects measured by Saccharomyces cerevisiae BLYES/BLYAS strains, respectively) of glyphosate, AMPA, polyethoxylated POE(15) and 13 GBHs from which 11 formulations do not contain polyethoxylated POE(15). Among the pure substances, neither glyphosate nor AMPA had any effects, while polyethoxylated POE(15) exhibited pronounced toxicity and was also estrogenic but not androgenic. Regarding the acute and chronic cytotoxicity and hormonal activity of GBHs, dilution percentages calculated from EC50 values were in the most cases by one or two order of magnitude lower than the minimum recommended dilution for agricultural and household use. Relation could not be observed between the biological effects and type of glyphosate-salts; hence toxicity could be linked to the co-formulants, which are not even declared in 3 GBHs. Toxicological evaluation must focus on these substances and free accessibility of GBHs should be reconsidered. Graphical abstract: Image 1 Highlights: 13 glyphosate-based herbicides (GBHs) cytotoxic and hormonal activity were studied. EC50 values converted to dilution% were compared to the directions for use of GBHs. GBHs are toxic and hormonally active below the minimal recommended dilution. Glialka Express 6H® with 1% of IPA salt and co-formulants is the most toxic GBH. Formulation-depending toxicity and hormonal activity was demonstrated. Abstract : Cytotoxicity and hormonal activity of glyphosate-based herbicides are linked to formulation. Biological effects appear at concentrations below the recommended dilutions.